Low Body Mass Index, Serum Creatinine, and Cause of Death in Patients Undergoing Percutaneous Coronary Intervention. Issue 11 (November 2016) - Goel, Kashish; Gulati, Rajiv; Reeder, Guy S.; Lennon, Ryan J.; Lewis, Bradley R.; Behfar, Atta; Sandhu, Gurpreet S.; Rihal, Charanjit S.; Singh, Mandeep
Abstract : Background: Low body mass index (BMI) and serum creatinine are surrogate markers of frailty and sarcopenia. Their relationship with cause‐specific mortality in elderly patients undergoing percutaneous coronary intervention is not well studied. Methods and Results: We determined long‐term cardiovascular and noncardiovascular mortality in 9394 consecutive patients aged ≥65 years who underwent percutaneous coronary intervention from 2000 to 2011. BMI and serum creatinine were divided into 4 categories. During a median follow‐up of 4.2 years (interquartile range 1.8–7.3 years), 3243 patients (33.4%) died. In the multivariable model, compared with patients with normal BMI, patients with low BMI had significantly increased all‐cause mortality (hazard ratio [HR] 1.4, 95% CI 1.1–1.7), which was related to both cardiovascular causes (HR 1.4, 95% CI 1.0–1.8) and noncardiovascular causes (HR 1.4, 95% CI 1.06–1.9). Compared with normal BMI, significant reduction was noted in patients who were overweight and obese in terms of cardiovascular mortality (overweight: HR 0.77, 95% CI 0.67–0.88; obese: HR 0.80, 95% CI 0.70–0.93) and noncardiovascular mortality (overweight: HR 0.85, 95% CI 0.74–0.97; obese: HR 0.82, 95% CI 0.72–0.95). In a multivariable model, in patients with normal BMI, low creatinine (≤0.70 mg/dL) was significantly associated with increased all‐cause mortality (HR 1.8, 95% CI 1.3–2.5) and cardiovascular mortality (HR 2.3, 95% CI 1.4–3.8) compared with patients with normal creatinine (0.71–1.0 mg/dL); however, this was not observed in other BMI categories. Conclusions: We identified a new subgroup of patients with low serum creatinine and normal BMI that was associated with increased all‐cause mortality and cardiovascular mortality in elderly patients undergoing percutaneous coronary intervention. Low BMI was associated with increased cardiovascular and noncardiovascular mortality. Nutritional support, resistance training, and weight‐gain strategies may have potential roles for these patients undergoing percutaneous coronary intervention.